Salicylates Ameliorate Intestinal Inflammation by Activating Macrophage AMPK. Issue 6 (30th November 2020) - Banskota, Suhrid; Wang, Huaqing; Kwon, Yun Han; Gautam, Jaya; Gurung, Pallavi; Haq, Sabah; Hassan, F M Nazmul; Bowdish, Dawn M; Kim, Jung-Ae; Carling, David; Fullerton, Morgan D; Steinberg, Gregory R; et al.
Abstract: Background: Inflammatory bowel diseases are the most common chronic intestinal inflammatory conditions, and their incidence has shown a dramatic increase in recent decades. Limited efficacy and questionable safety profiles with existing therapies suggest the need for better targeting of therapeutic strategies. Adenosine monophosphate-activated protein kinase (AMPK) is a key regulator of cellular metabolism and has been implicated in intestinal inflammation. Macrophages execute an important role in the generation of intestinal inflammation. Impaired AMPK in macrophages has been shown to be associated with higher production of proinflammatory cytokines; however, the role of macrophage AMPK in intestinal inflammation and the mechanism by which it regulates inflammation remain to be determined. In this study, we investigated the role of AMPK with a specific focus on macrophages in the pathogenesis of intestinal inflammation. Methods: A dextran sodium sulfate-induced colitis model was used to assess the disease activity index, histological scores, macroscopic scores, and myeloperoxidase level. Proinflammatory cytokines such as tumor necrosis factor-α, interleukin-6, and interleukin-1β were measured by enzyme-linked immunosorbent assay. Transient transfection of AMPKβ1 and LC3-II siRNA in RAW 264.7 cells was performed to elucidate the regulation of autophagy by AMPK. The expression of p-AMPK, AMPK, and autophagy markers (eg, LC3-II, p62, Beclin-1, and Atg-12) was analyzed by Western blot. Results: Genetic deletion of AMPKβ1 in macrophages upregulated the production of proinflammatory cytokines, aggravated the severity of dextran sodium sulfate-induced colitis in mice, which was associated with an increased nuclear translocation of nuclear factor-κB, and impaired autophagy both in vitro and in vivo. Notably, the commonly used anti-inflammatory 5-aminosalicylic acid (ie, mesalazine) and sodium salicylate ameliorated dextran sodium sulfate-induced colitis through the activation of macrophage AMPK targeting the β1 subunit. Conclusions: Together, these data suggest that the development of therapeutic agents targeting AMPKβ1 may be effective in the treatment of intestinal inflammatory conditions including inflammatory bowel disease.